Maximal Regularity Estimates and the Solvability of Nonlinear Differential Equations - Myrzagali Ospanov; Kordan Ospanov (Mathematics, 2022)
We study a type of third-order linear differential equations with variable and unbounded coefficients, which are defined in an infinite interval. We also consider a non-linear generalization with coefficients that depends on an unknown function. We establish sufficient conditions for the correctness of this linear equation and the maximal regularity estimate for their solution. Using these results, we prove the solvability of a nonlinear differential equation and estimate the norms of its terms.